Alain Badiou : Between Theology and Anti-Theology. - Phelps, Hollis (Routledge, 2014)
''Alain Badiou: Between Theology and Anti-theology'' provides one of the first comprehensive analyses of the relationship between Badiou''s philosophy and theology. Examining the full range of Badiou''s writings, this provocative study explores how Badiou''s philosophy relies on theology even if he claims otherwise and actively attempts to work against theology. Despite the complex questions discussed - ranging across ontology, the theory of truth and the subject, philosophy and its conditions, and anti-philosophy - this book presents a clear and accessible overview of the theological, rel.